Paraganglioma retroperitoneal no funcional - Gómez Galán, Sebastian; Mosquera Paz, Manuel Santiago; Kadamani Abiyomaa, Akram; Sánchez de Guzmán, Gabriel (Iatreia, 2014)
<!–[if gte mso 9]> Normal.dotm 0 0 1 149 852 Sabana 7 1 1046 12.0 <![endif]–><!–[if gte mso 9]> 0 false 21 18 pt 18 pt 0 0 false false false <![endif]–><!–[if gte mso 9]> <![endif]–> <!–[if gte mso 10]> <![endif]–> <!–StartFragment–> Retroperitoneal non-functional paraganglioma: Report of a case from the Cardioinfantil Foundation, Bogotá, Colombia Paragangliomas are tumors derived from chromaffin cells from the neural crest. They are able to secrete catecholamines, hormones and peptides. They can be found in the skull base, neck, thorax and abdomen, and may be functional or not-functional. We report the case of a male patient with non-specific pain in the right hypochondrium. Based on the initial imaginological studies a neuroblastoma was suspected, but it not possible to differentiate it from a paraganglioma, a ganglioneuroblastoma or a neurofibroblastoma. The pathological study of the surgical specimen revealed extensive hemorrhagic areas, consistent with a non-functional extra-adrenal paraganglioma. This is an infrequent neoplasia with difficult surgical treatment <!–EndFragment–>